Political Graffiti on the West Bank Wall in Israel - Olberg, Steven T. (The Edwin Mellen Press, 2012)
Based on field research conducted by the author in 2008, the book consists of a careful examination of graffiti written on both the Palestinian and Israeli sides of the Israel-built "separation wall"; and interviews with people about the graffiti. This shows how different sides of the conflict view the conflict itself and details the various ways that graffiti can represent political strife.